PENGARUH PEER GRUP EDUCATION TERHADAP TINGKAT PENGETAHUAN TENTANG PENANGANAN PREMENSTRUAL SYNDROME PADA REMAJA PUTRI KELAS VII SMP NEGERI 2 MOJOANYAR MOJOKERTO - Etik Khusniyati; Heni Purwati; Purwati Purwati (Bahasa Indonesia, 2017)
An adolescent’s knowledge about premenstrual syndrome handling is still in the minor level since parents have no intention to talk openly and it tends to be a taboo. A peer group education method can be used to give information on adolescent girl about premenstrual syndrome handling in which it can be taught more openly. This study aims at investigating the influence of peer group education toward level of premenstrual syndrome handling’s knowledge of adolescent girl. This study used pre-experimental design with One-Group Pre-Post Test Design. The number of population were 81 adolescent girls from VII grade in which taken by using probability sampling (cluster sampling). The number of sample it self were 66 respondents. The independent variable was peer group education and the dependent variable was level of adolescent premenstrual syndrome handling’s knowledge. The data were collected by using questioner which was used before and after peer group education. The data were processed after gaining the whole data collection and the statisticalWilcoxon sign test were used afterward. The findings revealed that the value of asymp.sig (2 tailed) was 0,000 and α was 0, 05. The value of asymp.sig (2-tailed) <α 0,05, it means that H1 was accepted in which there were influence of peer group education toward level of adolescent premenstrual syndrome handling’s knowledge in VII grade of state SMP 2 Mojoanyar Mojokerto. A peer group education method stimulated both peer educator and peer group to discuss and share information each other about the problems of premenstrual syndrome handling openly in order to increase their knowledge.